Sustainable prosperity and enterprises for Maori communities in Aotearoa New Zealand: a review of the literature. Issue 4 (18th June 2021) - Neha, Tia; Macfarlane, Angus; Macfarlane, Sonja; Clarke, Te Hurinui; Derby, Melissa; Torepe, Toni; Duckworth, Fiona; Gibson, Marie; Whelan, Roisin; Fletcher, Jo
Abstract : Purpose: The research in the field of Indigenous peoples and the espousal of their cultural values in the work environment is recognised as being important as a means of overcoming workplace inequities. The purpose of this paper is to examine research about Maori, the Indigenous people of Aotearoa New Zealand that may inform future enterprises for the long-term prosperity of marginalised Indigenous peoples. Design/methodology/approach: This study reviews the literature on unique cultural dynamics of whanau Maori (New Zealand Maori family/community) study practices and the importance of work/home/life balance. Furthermore, it considers strengths-based community enterprises that can lead to sustainable prosperity for Maori. Findings: The review yielded three theoretical principles that explain mana (sociocultural and psychological well-being), which can be generalised across multiple contexts, with the workplace being one of these contexts. These principles of mana create a contextual match with whanau external realities; an experiential match of a mana empowerment framework that transfers to the study context and an interpersonal understanding of being understood and empowered within the study context. Research limitations/implications: The literature review has been limited to research from 2005 onwards and to research that investigates Maori, the Indigenous peoples of Aotearoa New Zealand. Although the review of the literature has these limitations, the review may be of interest to other studies of Indigenous peoples worldwide. Practical implications: The key factors are interwoven, and their importance is considered in relation to the development of positive and supportive environments, which link to job retention, satisfaction and productivity in the workplace for Maori. This, in turn, can have beneficial knock-on effects for not only the New Zealand economy but also more importantly for enhancing sustainable livelihoods for upcoming generations. Social implications: Tied together, these factors are paramount for cultural, social and ecological benefits for nga rangatahi (young Maori adults) and the wider community in the workplace. Originality/value: The literature review's value and originality derive from a dearth of recent research on supporting nga rangatahi (young Maori adults) for sustainable prosperity.